Pseudomonas aeruginosa Lipoxygenase LoxA Contributes to Lung Infection by Altering the Host Immune Lipid Signaling - Morello, Eric; Pérez-Berezo, Teresa; Boisseau, Chloé; Baranek, Thomas; Guillon, Antoine; Bréa, Déborah; Lanotte, Philippe; Carpena, Xavier; Pietrancosta, Nicolas; Hervé, Virginie; Ramphal, Reuben; Cenac, Nicolas; et al. (Frontiers in Microbiology, 2019)
Pseudomonas aeruginosa is an opportunistic bacteria and a major cause of nosocomial pneumonia. P. aeruginosa has many virulence factors contributing to its ability to colonize the host. LoxA is a lipoxygenase enzyme secreted byP. aeruginosa that oxidizes polyunsaturated fatty acids. Based on previous in vitro biochemical studies, several biological roles of LoxA have been hypothesized, including interference of the host lipid signaling and modulation of bacterial invasion properties. However, the contribution of LoxA to P.aeruginosa lung pathogenesis per se remained unclear. In this study, we used complementary in vitro and in vivo approaches, clinical strains of P. aeruginosa as well as lipidomics technology to investigate the role of LoxA in lung infection. We found that several P. aeruginosa clinical isolates express LoxA. When secreted in the lungs, LoxA processes a wide range of host polyunsaturated fatty acids, which further results in the production of bioactive lipid mediators (including lipoxin A4). LoxA also inhibits the expression of major chemokines (e.g. MIPs and KC) and the recruitment of key leukocytes. Remarkably, LoxA promotes P. aeruginosa persistence in lungs tissues. Hence, our study suggests that LoxA-dependent interference of the host lipid pathways may contribute to P. aeruginosa lung pathogenesis